Для начала упростим выражение.
(-13/15 a^4 b^2)^2 = (-13/15 (-1 6/7)^4 (7/13)^2)^2 = (-13/15 (-55/7)^4 49/169)^2 = (-13/15 60025/2401 49/169)^2 = (-13/15 14.97 49/169)^2 ≈ (-13/15 14.97 0.28)^2 ≈ -0.32
(15/26 a^3 b^4)^3 = (15/26 (-1 6/7)^3 (7/13)^4)^3 = (15/26 (-55/7)^3 2401/28561)^3 = (15/26 -166375/343)^3 = (15/26 -4850.61)^3 ≈ -82.15
Теперь найдем значение выражения: -0.32 * -82.15 = 26.448
Таким образом, значение выражения (-13/15 а^4 b^2)^2 * (15/26 a^3 b^4)^3 при a = -1 6/7 и b = 7/13 равно 26.448.